Optimizing Smartphone Use in Outdoor Learning Activities for Coastal Conservation Education - Khusnul Basriyah; Rama Dona (Jurnal Praktik Baik Pembelajaran Sekolah dan Pesantren, 2026)
Coastal environmental degradation has become an increasingly urgent issue in many suburban and peripheral areas. However, environmental learning in schools is often conducted theoretically and lacks direct student engagement with real ecological problems. This best practice article describes the implementation of smartphone-assisted outdoor learning activities aimed at improving students’ awareness and understanding of coastal conservation. The activity was conducted in a suburban coastal area involving secondary school students through field observation, environmental documentation, digital reporting, and reflective discussion. Smartphones were utCoastal environmental degradation has become an increasingly urgent issue in many suburban and peripheral areas. However, environmental learning in schools is often conducted theoretically and lacks direct student engagement with real ecological problems. This best practice article describes the implementation of smartphone-assisted outdoor learning activities aimed at improving students’ awareness and understanding of coastal conservation. The activity was conducted in a suburban coastal area involving secondary school students through field observation, environmental documentation, digital reporting, and reflective discussion. Smartphones were utilized as tools for photographing environmental conditions, recording observations, accessing digital information, and creating conservation campaigns. The results indicated increased student participation, stronger environmental awareness, improved collaboration, and higher learning motivation. Students demonstrated better understanding of coastal ecosystem problems such as plastic pollution and shoreline degradation. Furthermore, the integration of mobile technology into outdoor learning created a more contextual, interactive, and student-centered learning environment. This article highlights the potential of smartphones as accessible educational tools in environmental education and recommends broader implementation of technology-supported outdoor learning for sustainability education in coastal communities.ilized as tools for photographing environmental conditions, recording observations, accessing digital information, and creating conservation campaigns. The results indicated increased student participation, stronger environmental awareness, improved collaboration, and higher learning motivation. Students demonstrated better understanding of coastal ecosystem problems such as plastic pollution and shoreline degradation. Furthermore, the integration of mobile technology into outdoor learning created a more contextual, interactive, and student-centered learning environment. This article highlights the potential of smartphones as accessible educational tools in environmental education and recommends broader implementation of technology-supported outdoor learning for sustainability education in coastal communities.